The moral conceptions of José Martí about Physical Education, Sports and Recreation/Las concepciones morales de José Martí acerca de la Educación Física, el Deporte y la Recreación - Juan Carlos Hernández Martín; Isabel Reinoso Castillo (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2022)
Introduction: José Martí, Cuba's national hero, has bequeathed various progressive perspectives over time, including in sports, a lesser-known facet of his prolific journalistic and literary work. It is known that he practiced a single specialty: chess; but in his chronicles he demonstrated knowledge of long-distance running, American football, billiards, boxing, horse riding, fencing, hunting, bullfighting and skating, among others. Objective: To deepen the moral conceptions of the National Hero of Cuba about sports and Physical Education. Material and method: to carry out this study, a bibliographic review of the complete works of José Martí was developed, referring to the North American scenes where Martí's chronicles about sports and Physical Education are collected to a greater extent. Results: The topic that is addressed by his interest transcends the borders of his time and is inserted in the project of the ideas that sustain the Cuban revolution, that sport is a right of the people; This article is dedicated to this, to highlight the opinions expressed by José Martí on sports, Physical Education and Recreation, being a critic of these from the moral point of view. Conclusions: José Martí developed an arsenal of ideas that constitute a high contribution to the development of sport and Physical Education. In journalism, the teacher had one of the most accurate views on the practice of sport.